Progress in copper-catalyzed trifluoromethylation - Li, Guan-bao; Zhang, Chao; Song, Chun; Ma, Yu-dao (Beilstein Journal of Organic Chemistry, 2018)
The introduction of trifluoromethyl groups into organic molecules has attracted great attention in the past five years. In this review, we describe the recent efforts in the development of trifluoromethylation via copper catalysis using nucleophilic, electrophilic or radical trifluoromethylation reagents.
Keywords: copper; fluorine; trifluoromethylation